Effect of Diaphragm Strengthening Exercise with Incentive Spirometry on Pain and Core Muscle Stability in Low Back Pain Patients at M.Yunus Hospital Bengkulu - Eca Putri Sukamto; Riry Ambarsarie; Zayadi Zainuddin; Ahmad Azmi Nasution; Diah Ayu Aguspa (Indonesian Journal of Health Research and Development, 2024)
This study examined the effect of diaphragm strengthening exercise with incentive spirometry on pain and core muscle stability in patient with LBP (Low Back Pain). Twenty respondents aged 25-60 years participated in this research group. This research using a pre-experimental one-group pretest-posttest design. Incentive spirometry training was given to one group 3 times a week for 4 weeks. Pain level was measured using the numerical rating scale and core muscle stability was measured using a sphygmomanometer which had been modified to function as a tool to measure core muscle stability. There was a decrease in pain levels and an increase in core muscle stability in research subjects. The results of the wilcoxon test and paired t-test obtained a significance value of less than 0.05. There is an effect of diaphragm muscle strengthening exercises using incentive spirometry on improving pain and core muscle stability in patients with LBP (Low Back Pain).